Internet Memes and the Framing of the Gaza War: Perspectives from Media Narratives - Joseph Ifeoluwa Joy; Abdullahi Aliyu Maiwada; Mohammed Jibril Nasir (Budapest International Research and Critics University, 2026)
The increasing prominence of social media has transformed the production, circulation, and consumption of information during armed conflicts, with internet memes emerging as influential tools of digital communication and political expression. This study examines how internet memes framed the Gaza War across international digital spaces and explores the dominant narratives embedded within these visual and textual artifacts. Grounded in Framing Theory, the paper investigates the ways in which memes construct, reinforce, and contest interpretations of the conflict among global online audiences. The study adopts a qualitative comparative research design and relies on secondary data drawn from existing scholarly literature, reports, digital archives, and publicly available meme collections circulated on major social media platforms, including X (formerly Twitter), Instagram, Facebook, and Reddit during key periods of the conflict. Through thematic and frame analysis, the study identifies recurring frames such as humanitarian crisis, resistance and liberation, victimhood, geopolitical contestation, media bias, and international solidarity. The findings reveal significant variations in meme narratives across different geopolitical and cultural contexts, reflecting divergent ideological positions and media environments. While some memes foreground civilian suffering and humanitarian concerns, others emphasize national security, political resistance, or criticism of international actors and mainstream media institutions. The study further demonstrates that memes function not merely as humorous content but as powerful communicative devices that simplify complex geopolitical issues, facilitate transnational engagement, and shape public perceptions of conflict. The research contributes to the growing body of literature on digital media, conflict communication, and participatory political discourse by highlighting the role of user-generated visual content in the framing of contemporary wars. It concludes that internet memes have become significant alternative mechanisms for international conflict coverage, influencing how audiences interpret events beyond traditional news media frameworks. The study recommends greater scholarly attention to meme culture as an emerging force in global political communication and digital conflict reporting.